Piccolo Promotes Vesicle Replenishment at a Fast Central Auditory Synapse - Butola, Tanvi; Wichmann, Carolin; Moser, Tobias (Frontiers in Synaptic Neuroscience, 2017)
Piccolo and Bassoon are the two largest cytomatrix of the active zone (CAZ) proteins involved in scaffolding and regulating neurotransmitter release at presynaptic active zones (AZ), but have long been discussed as being functionally redundant. We employed Cre-mediated genetic manipulation to bring forth and segregate the role of Piccolo from that of Bassoon at central auditory synapses of the cochlear nucleus – the endbulbs of Held. These synapses specialize in high frequency synaptic transmission, ideally poised to reveal even subtle deficits in the regulation of neurotransmitter release upon molecular perturbation. Combining semi-quantitative immunohistochemistry, electron microscopy, and in vitro and in vivo electrophysiology we first studied signal transmission in Piccolo-deficient mice. Our analysis was not confounded by a cochlear deficit, as a short isoform of Piccolo (‘Piccolino’) present at the upstream ribbon synapses of cochlear inner hair cells, is unaffected by the mutation. Disruption of Piccolo increased the abundance of Bassoon at the AZs of endbulbs, while that of RIM1 was reduced and other CAZ proteins remained unaltered. Presynaptic fiber stimulation revealed smaller amplitude of the evoked excitatory postsynaptic currents (eEPSC), while eEPSC kinetics as well as miniature EPSCs (mEPSCs) remained unchanged. Cumulative analysis of eEPSC trains indicated that the reduced eEPSC amplitude of Piccolo-deficient endbulb synapses is primarily due to a reduced readily releasable pool (RRP) of synaptic vesicles (SV), as was corroborated by a reduction of vesicles at the active zones found on an ultrastructural level. Release probability seemed largely unaltered. Recovery from short-term depression was slowed. We then performed a physiological analysis of endbulb synapses from mice which, in addition to Piccolo deficiency, lacked one functional allele of the Bassoon gene. Analysis of the double-mutant endbulbs revealed an increase in release probability, while the synapses still exhibited the reduced RRP, and the impairment in SV replenishment was exacerbated. We propose additive roles of Piccolo and Bassoon in SV replenishment which in turn influences the organization and size of the RRP, and an additional role of Bassoon in regulation of release probability.